2016
DOI: 10.1021/jacs.6b09533
|View full text |Cite
|
Sign up to set email alerts
|

Alcohols as Latent Coupling Fragments for Metallaphotoredox Catalysis: sp3–sp2 Cross-Coupling of Oxalates with Aryl Halides

Abstract: Alkyl oxalates, prepared from their corresponding alcohols, are engaged for the first time as carbon radical fragments in metallaphotoredox catalysis. In this report, we demonstrate that alcohols, native organic functional groups, can be readily activated with simple oxalyl chloride to become radical precursors in a net redox-neutral Csp3–Csp2 cross-coupling with a broad range of aryl halides. This alcohol-activation coupling is successfully applied to the functionalization of a naturally occurring steroid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
117
1
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(132 citation statements)
references
References 33 publications
5
117
1
3
Order By: Relevance
“…[84] Similar to those in their previous work, the mechanism involves an oxidative SET substrate activation event from Ir III * to afford the key radical intermediate, which is then intercepted either by an Ni 0 catalyst or by an Ni II species derived from the aryl bromide. A wide range of unactivated secondary alcohols were compatible with the protocol, including the steroid pregnenolone and an intermediate in the synthesis of Q203, an antituburcular compound with promising in vitro and in vivo pharmacodynamics and pharmacokinetic properties.…”
Section: C(sp 3 )-Alcohol Derivativesmentioning
confidence: 63%
“…[84] Similar to those in their previous work, the mechanism involves an oxidative SET substrate activation event from Ir III * to afford the key radical intermediate, which is then intercepted either by an Ni 0 catalyst or by an Ni II species derived from the aryl bromide. A wide range of unactivated secondary alcohols were compatible with the protocol, including the steroid pregnenolone and an intermediate in the synthesis of Q203, an antituburcular compound with promising in vitro and in vivo pharmacodynamics and pharmacokinetic properties.…”
Section: C(sp 3 )-Alcohol Derivativesmentioning
confidence: 63%
“…Moreover, several studies have demonstrated that photoredox and transition-metal catalysis can be successfully merged (metallaphotoredox) to deliver many selective native-group functionalizations, including decarboxylative and deoxygenative couplings 21,22 . Photoredox catalysis was recently used to address the issue of native C–H functionalization by taking advantage of the polarity matching effect, a subtle yet important element in HAT catalysis 23 .…”
mentioning
confidence: 99%
“…[40] Die Oxalsäure als Redoxagens agiert analog zu Carbonsäuren. [40] Die Oxalsäure als Redoxagens agiert analog zu Carbonsäuren.…”
Section: Kupplungen Mit Carbonsäuren Als Radikalvorstufenunclassified